(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
High demands are placed on therapeutic nutrition, since the kidneys are the main organ for the excretion of metabolic products received with food and formed as a result of the breakdown of body tissues, as well as the organ responsible for maintaining the constancy of the internal environment. Under certain conditions, there is a need to correct in the diet such nutrients as animal protein, gluten, urates, oxalates, phosphates, the metabolic products of which are excreted through the kidneys and affect not only the pathogenetic mechanisms of disease development, but also participate in the formation of non-immune processes of disease progression to the stage of renal failure. Objective of the study: to study the features of the development of oxalate nephropathy in children and to identify the relationship with gastrointestinal pathology. Materials and methods. We examined 66 children with oxalate nephropathy aged 5 to 16 years, living in the Samarkand region. All children underwent general clinical examinations, biochemical blood and urine tests. To assess the condition of the gastrointestinal mucosa, patients underwent ultrasound examination of the parenchymatous organs, stool examination for dysbacteriosis. Esophagogastroduodenoscopy.